Modified Spin Column-Based RNA Extraction Methods of Staphylococcus aureus using PureLink® RNA Mini Kit and Basic Laboratory Instrument - Muhammad Taufiq Hidayat; Endry Nugroho Prasetyo (Universitas Nahdlatul Ulama Surabaya, 2021)
RNA extraction is an important process before gene expression assessment at the transcriptomic level. RNA is a sensitive material to environmental factors such as temperature and contaminants, so the RNA extraction process generally requires sophisticated and expensive laboratory instruments. In this study, we extract RNA from Staphylococcus aureus bacteria using the PureLink® RNA Mini Kit. The instruments used in this study are basic instruments such as a hand homogenizer and non-thermal centrifuge. The results of RNA extraction were visualized using agarose gel electrophoresis. These results indicate that bacterial RNA extraction can be performed using the PureLink® RNA Mini Kit even with inexpensive basic laboratory instruments.